2017
DOI: 10.1039/c7cp06638d
|View full text |Cite
|
Sign up to set email alerts
|

Different dominant transitions in holmium and ytterbium codoped oxyfluoride glass and glass ceramics originating from varying phonon energy environments

Abstract: Transparent oxyfluoride glass and glass ceramics doped with 0.5% Ho and 1.0% Yb ions have been prepared. X-ray diffraction and transmission electron microscopy demonstrated the formation of NaYF nanocrystals during the heat treatment process. Raman spectra indicated the variation of glass structure brought about by the formation of NaYF nanocrystals. XRD curves and Judd-Ofelt intensity parameters confirmed the incorporation of Ho into NaYF nanocrystals. Significantly enhanced visible upconversion and 2.85 μm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The calculation results showed that the peak absorption cross section reached 9.93×10 -21 cm 2 at 2880 nm, while the peak emission cross section reached 11.18×10 -21 cm 2 at 2888 nm which is higher than that of oxyfluoride silicate GC(6.0×10 -21 cm 2 ) 4 . Obviously, it can be attributed to the higher density of oxyfluoride germanosilicate GC, as there is a positive correlation between density and absorption and emission cross sections.…”
Section: Mid-infrared Emission Propertiesmentioning
confidence: 81%
See 3 more Smart Citations
“…The calculation results showed that the peak absorption cross section reached 9.93×10 -21 cm 2 at 2880 nm, while the peak emission cross section reached 11.18×10 -21 cm 2 at 2888 nm which is higher than that of oxyfluoride silicate GC(6.0×10 -21 cm 2 ) 4 . Obviously, it can be attributed to the higher density of oxyfluoride germanosilicate GC, as there is a positive correlation between density and absorption and emission cross sections.…”
Section: Mid-infrared Emission Propertiesmentioning
confidence: 81%
“…For SiO 2 -rich glass and glass ceramics, the upconversion emissions and NIR emission are both enhanced with the heat-treatment temperature. This is because more rare earth ions located at fluoride nanocrystals with low phonon energy, in which the multi-phonon assisted non-radiative decay rates is significantly reduced so that the radiative emission is enhanced 4,22,23 . For GeO 2 -rich glass and glass ceramics, the upconversion emission and NIR emission of glass ceramics are stronger than those of the precursor glass, but not shown a positive correlation with the heat-treatment temperature because there is no similar fluoride nanocrystallization.…”
Section: Vis-nir Emission Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulated emission cross section σ em is one of the most basic physical quantities to evaluate the energy extraction e ciency from rare-earth doped optical materials, not only for a fundamental understanding of the excitation and depopulation process but also for the optimization of laser materials, which is determined through the Fuchtbauer-Ladenburg equation [60]:…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%